Aerodynamic design, optimization and acoustic analysis of a turbine rear structure - Wikerby, Emma-Liisa (My University, 2024)
Noise emissions emanating from aircraft engines in urban areas has long been a concern. For this thesis the Turbine Rear Structure (TRS) of a turbofan engine is designed with the aim of reducing noise emission and total pressure losses. The aerodynamic functionality of the TRS is to de-swirl the upstream flow coming from the low pressure turbine to maximize the thrust for varying loading conditions. The objectives are thus to construct an aerodynamic design that work well at on- and off-design conditions and analyze the effect of leaned guide vanes on noise emissions. Through a Design of Experiment a design matrix is constructed with varied geometrical parameters for the guide vanes and endwalls by running the designs in a 3D solver. The design matrix gives the subspace for optimizing the TRS towards the objectives of this thesis by applying criterion on performance parameters. With an optimized design at the different loading conditions, lean is applied to the guide vanes and the effect of lean is then analyzed on the performance and noise emissions for the TRS.
Keywords: TRS; design of experiment; guide vanes; pressure loss; lean; aerodynamic performance; noise emissions